Recent Advances in Solid-Electrolyte Interphase for Li Metal Anode - He, Dafang; Lu, Junhong; He, Guangyu; Chen, Haiqun (Frontiers in Chemistry, 2022)
Lithium metal batteries (LMBs) is considered to be a substitute for Lithium-ion batteries (LIBs) and the next-generation battery with high energy density. However, the commercialization of LMBs is serious impeded by uncontrollable growth of dangerous lithium dendrites during long-term cycling. The generation and growth of lithium dendrites are mainly derived from unstable solid-electrolyte interphase (SEI) layer on metallic lithium anode. SEI layer is a key by-product formed on the surface of lithium metal anode during the electrochemical reactions, and has been the barrier of the development in this area. An ideal SEI layer should possess electrical insulating, superior mechanical modulus, high electrochemical stability, and excellent Li-ion conductivity, which could improve the structure stability of electrode upon a long-time cycling. This mini-review carefully summarizes the recent developments in SEI layer for LMBs, and the relationship between SEI layer optimization and electrochemical property is also discussed. In addition, the further development direction of stable SEI layer is also proposed.